The dual benefit of first aid training among Civilians in a time of war. (1st March 2011) - Jaffe, E; Aviel, E; Kodinsky, N; Knobler, H; Aharonson-Daniel, L
Abstract : Background: First-aid training enables the acquisition of life-saving skills. However, proficiency in first-aid also reduces anxiety among caregivers. The question explored in this study was as follows: Will first-aid training in shelters to civilians under missile attacks contribute to reducing anxiety among the trainees beyond the provision of life-saving skills? Methods: Participants of first-aid training courses conducted in shelters in settlements under missile attack in southern Israel during January 2009 were asked about their reason for joining the course, the quality of training, the courses' influence on their perceived role during a missile attack and their self perceived proficiency with life-saving skills. Results: 140 respondents, residents of 28 southern settlements of whom 77% were female. The training course significantly contributed to the feeling of safety, the knowledge what to do after a missile attack and role acquisition. The quality of training was found to contribute to reducing anxiety with the knowledge variable as a mediator. Conclusions: People under attack, who learnt first-aid while in bomb-shelters, perceived themselves as caregivers and not as potential targets of attack themselves. Learning first-aid is seen as a mode to enable helping loved-ones, but not as a way of reducing anxiety among trainees. The professional level of training significantly influences the level of knowledge, and thus decreases anxiety. The aspiration to use good instructors always exists. This study emphasises the great importance of assigning appropriate instructors in such situations.